2013
DOI: 10.2174/1573406411309050013
|View full text |Cite
|
Sign up to set email alerts
|

3-Methyl-6-(prop-1-en-2-yl)cyclohex-3-ene-1,2-diol: the Importance of Functional Groups for Antiparkinsonian Activity

Abstract: Compounds with different sets of three of the four functional groups of (1R,2R,6S)-3-methyl-6-(prop-1-en-2- yl)cyclohex-3-ene-1,2-diol 1 possessing high antiparkinsonian activity were synthesized. The synthesized compounds were tested for the antiparkinsonian activity in vivo on a mouse model with MPTP neurotoxin. A pronounced antiparkinsonian effect of 1 can only be achieved if it contains all the four functional groups (two hydroxy groups and two double bonds). The 2-hydroxy group or the 3,4-double bond is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…[10][11][12] We synthesized and tested in vivo a number of derivatives, including all eight stereoisomers of compound 1. 13 It was found that all of the four functional groups of 1 are needed for the compound to exhibit anti-PD activity. Among N-, O-, S-and C-derivatives at the C9 position of diol 1, compounds 2 and 3 with butyl or propylthio substituents exhibited a high activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] We synthesized and tested in vivo a number of derivatives, including all eight stereoisomers of compound 1. 13 It was found that all of the four functional groups of 1 are needed for the compound to exhibit anti-PD activity. Among N-, O-, S-and C-derivatives at the C9 position of diol 1, compounds 2 and 3 with butyl or propylthio substituents exhibited a high activity.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously discovered a small low-toxicity molecule (1 R ,2 R ,6 S )-3-methyl-6-(prop-1-en-2-yl)­cyclohex-3-ene-1,2-diol 1 (Figure ) that can potently alleviate motor symptoms in rodent models of PD. We synthesized and tested in vivo a number of derivatives, including all eight stereoisomers of compound 1 . It was found that all four functional groups of 1 are needed for the compound to exhibit anti-PD activity . Among N-, O-, S-, and C-derivatives at the C9 position of diol 1 , compounds 2 and 3 with butyl or propylthio substituents exhibited a high activity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute configuration of 1 affected its anti-Parkinson's activity [1]. It was important to include all functional groups (double bonds and hydroxyls) in the molecule [3]. Metabolism studies represent a key phase of pharmacokinetic investigations.…”
mentioning
confidence: 99%
“…Very effective methods for adding and removing pyranyl protection using In(OTf) 3 [17] and (NH 4 ) 2 Ce(NO 3 ) 6 (CAN) [18] as catalysts were described. Use of In(OTf) 3 , CAN, or PPTS in various solvents to remove THP from stereomers 9 was accompanied by secondary and/or side reactions and formed complicated product mixtures.…”
mentioning
confidence: 99%